Circle Method for Robust Estimation of Local Conduction Velocity High-Density Maps From Optical Mapping Data: Characterization of Radiofrequency Ablation Sites - Siles-Paredes, Jimena G.; Crowley, Christopher J.; Fenton, Flavio H.; Bhatia, Neal; Iravanian, Shahriar; Sandoval, Italo; Pollnow, Stefan; Dössel, Olaf; Salinet, João; Uzelac, Ilija (Frontiers in Physiology, 2022)
Conduction velocity (CV) slowing is associated with atrial fibrillation (AF) and reentrant ventricular tachycardia (VT). \hl{Clinical} electroanatomical mapping systems used to localize AF or VT sources as ablation targets remain limited by the number of \hl{measuring} electrodes and signal processing methods to generate high-density local activation time (LAT) and CV maps of heterogeneous atrial or trabeculated ventricular endocardium. The morphology and amplitude of bipolar electrograms depend on the direction of \hl{propagating electrical} wavefront, \hl{making identification of} low-amplitude signals sources commonly associated with fibrotic areas \hl{difficult}. In comparison, unipolar electrograms are not sensitive \hl{to wavefront direction, but measurements are susceptible to distal} activity. This study proposes a \hl{method} for local CV calculation from optical mapping measurements, termed the circle method (CM). The local CV is obtained, \hl{as a weighted sum of CV values} calculated along different chords spanning a circle of predefined radius centered at \hl{CV measurement location}. As a distinct \hl{maximum in LAT differences} is along the chord normal to the propagating wavefront, the method \hl{is adaptive} to the propagating wavefront direction changes, suitable for \hl{electrical conductivity} characterization of heterogeneous myocardium. In numerical simulations, \hl{CM was validated characterizing} modeled ablated areas \hl{as zones of distinct CV slowing}. Experimentally, \hl{CM was used to characterize lesions created by} radio-frequency ablation (RFA) on isolated hearts of rats, guinea pig, and explanted human hearts. To infer the depth of RFA-created lesions, excitation light bands of different penetration depths were used, and a beat-to-beat CV difference analysis was performed \hl{to identify CV alternans}. Despite being limited to laboratory research, \hl{studies based on CM with optical mapping} may lead to new translational insights toward better-guided ablation therapies.